Trade Liberalization and Labor Market Adjustment in Brazil - Pavcnik, Nina; Blom, Andreas; Goldberg, Pinelopi; Schady, Norbert (World Bank, Washington, DC, 2014)
The authors study the impact of the 1988-94 trade liberalization in Brazil on wage distribution. They explore three main channels through which trade liberalization could have affected wage distribution: (1) increasing returns to skilled workers because of Hecksher-Ohlin adjustments to trade policy; (2) trade-induced skill-biased technological change; and (3) changes in industry wage premiums. The results suggest that trade reform in Brazil did contribute to the growing skill premium through skill-biased technological change, which was partially instigated by increased foreign competition. The authors also find that sector-specific returns to skill increased more in sectors with bigger tariff reductions. But they find little support for Hecksher-Ohlin type adjustments to trade reform. Overall, the effects of trade reform on wage inequality seem relatively small.